Analysis of Color and Chemical Oxygen Demand (COD) in Textile Industry Wastewater: Analisis Warna dan Chemical Oxygen Demand (COD) pada Air Limbah Industri Tekstil - Mareta Nur Shinta Dewi; Suseno (Jurnal Kimia dan Rekayasa, 2023)
Industry Textile including in Industry big that produces many waste especially waste water with content ingredient organic big who has color thick , smelly , and high Chemical Oxygen Demand (COD) , so that the waste water the should need processed more formerly before released to body of water with Fulfill raw the quality that has been set . Study this aim for knowing wastewater quality _ industry textile A if compared with raw quality according to Regulation Minister Environment Life and Forestry Republic of Indonesia Number P.16/MENLHK/SETJEN/KUM.1/4/ 2019 concerning Wastewater Quality Standards . Parameters studied is the color parameter with method spectrophotometry (SNI 6989.80:2011) and Chemical Oxygen Demand (COD) parameters with method spectrophotometry (SNI 6989.2:2019). After conducted study obtained score color of 4,277.5 Pt-Co and the value of Chemical Oxygen Demand (COD) is 1.640 mg O 2 /L. From result these two parameters , can be concluded that score color and the COD exceed raw quality according to Regulation Minister Environment Life and Forestry Republic of Indonesia Number P.16/MENLHK/SETJEN/KUM.1/4/ 2019 concerning Wastewater Quality Standards.AbstrakIndustri Tekstil termasuk dalam Industri besar yang menghasilkan banyak limbah terutama air limbah dengan kandungan bahan organik besar yang memiliki warna pekat, berbau, serta Chemical Oxygen Demand (COD) yang tinggi, sehingga air limbah tersebut sebaiknya perlu diolah terlebih dahulu sebelum dilepas ke badan air dengan memenuhi baku mutu yang telah ditetapkan. Penelitian ini bertujuan untuk mengetahui kualitas air limbah industri tekstil A jika dibandingkan dengan baku mutu menurut Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.16/MENLHK/SETJEN/KUM.1/4/2019 tentang Baku Mutu Air Limbah. Parameter yang diteliti ialah parameter warna dengan metode spektrofotometri (SNI 6989.80:2011) dan parameter Chemical Oxygen Demand (COD) dengan metode spektrofotometri (SNI 6989.2:2019). Setelah dilakukan penelitian didapatkan nilai warna sebesar 4.277,5 Pt-Co dan nilai Chemical Oxygen Demand (COD) sebesar 1.640 mg O2/L. Dari hasil kedua parameter tersebut, dapat disimpulkan bahwa nilai warna dan COD tersebut melebihi baku mutu menurut Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.16/MENLHK/SETJEN/KUM.1/4/2019 tentang Baku Mutu Air Limbah.